PENGGUNAAN MEDIA PEMBELAJARAN I-SPRING PRESENTER UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN HASIL BELAJAR PADA MATA KULIAH KEPERAWATAN DASAR NUTRISI - Alfiyansah, Rudy (PEDAGOGIA, 2016)
The low learning motivation and learning outcomes in basic nursing courses in addition to the material presented allegedly less attractive, as well as lectures, Â is not supported by appropriate learning media. Through this research will study whether the use of a computer learning media presenter i-spring can increase learning motivation and learning outcomes of students. This research is expected to produce a concept of learning by utilizing i-spring media presenter. The study was conducted using a quantitative approach with quasi-experimental design methods to develop nonequivalent control group design. The instrument used in this study, questionnaires and tests. By using the Test Statistic t, a picture that media are learning the material on the nutritional needs of basic nursing courses using instructional media i-spring presenter, can significantly increase student motivation and learn outcomes. Based on these results was a recommendation to the faculty, it would be better if the learning media i-spring presenter in completing the application program powerpoint. Those materials other lectures. Because the use of instructional media, the students not only enthusiastic (motivated) interact in lectures but shows the results of evaluation of the learning increased. Because the medium of learning many forms and types, in addition to the i-spring presenter, For next researchers can examine the factors - factors that affect learning computer i-spring presenter and study the development of e-learning with one i-spring program presenters included